Silica Monolayer Formation and Stability Determined by in situ Streaming Potential Measurements. (10th July 2016) - Morga, Maria; Adamczyk, Zbigniew; Kosior, Dominik
Graphical abstract: Highlights: Silica nanoparticle monolayers of controlled coverage were deposited on PAH-covered mica. Electrokinetic properties of the monolayers were thoroughly characterized in situ via streaming potential measurements. The stability of silica monolayers under flow conditions was determined. Binding energies of silica nanoparticles were quantitatively determined. A robust method of determining the coverage and electrokinetic properties of silica nanoparticle films was developed. Abstract: Silica nanoparticle monolayers on mica modified by poly(allylamine hydrochloride) (PAH) were deposited under diffusion-controlled transport in the electrokinetic cell. The zeta potential of the monolayers was determined by streaming potential measurements carried out under in situ (wet) conditions. These measurements, performed for various ionic strengths and pH, were quantitatively interpreted in terms of the three-dimensional (3D) electrokinetic model. Analogously, using streaming potential and AFM methods, the particle desorption kinetic under flow conditions was studied as a function ionic strength. This allowed one to determine the equilibrium adsorption constant Ka and the binding energy ϕm (energy minima depth) of silica particles, which is prohibitive for other experimental methods. The binding energies of the particles were calculated for various physicochemical conditions. It was shown that the energy was equal to −21 kT, being practically independent of ionic strength and pH. The experimental data indicates that the deposition kinetics of silica particles was governed by the electrostatic interactions among ion pairs. A practical aspect of these monolayer investigations consisted in formulating principles of a convenient method of thorough electrokinetic characterization of nanoparticles and their monolayers. Such monolayers may find practical applications as substrates for selective protein and nanoparticle deposition, sensors and photoelectrodes in various catalytic applications.